Multicaloric effect: Toward a breakthrough in cooling technology. (15th December 2018) - Czernuszewicz, Agata; Kaleta, Jerzy; Lewandowski, Daniel
Highlights: Direct measurement of multicaloric effect is presented. Magnetocaloric and barocaloric phenomena were combined. Multicaloric stimulation significantly reduces required magnetic and stress fields. Stress addition decreased the mass of magnets by up to two orders of magnitude. Abstract: Caloric cooling has significant potential to become an environmentally friendly and highly efficient alternative to conventional vapor-compression technology, however, this refrigeration method still remains in the stage of research. Adoption has been limited mainly due to the very high cost of cooling systems components. One possibility for reducing the price while improving system performance is the stimulation of a refrigerant material with more than one physical field; multicaloric refrigerators. Here we show, for the first time, the multicaloric effect determined for combined magnetocaloric and mechanocaloric phenomena. The effect was demonstrated using the Ni-Mn-In Heusler alloy and novel test system. The obtained temperature change is the sum of the independently measured phenomena. The multicaloric material stimulation can achieve a given result with 75% lower magnetic field compared to only the magnetocaloric transition and 30% lower stress relative to solely the mechanocaloric effect. This work proves the great promise of caloric refrigeration and provides a way to better understand the multicaloric temperature response of materials.